Atributos ODS para o desenvolvimento sustentável: um modelo para os portos brasileiros - COSTA, Markus Dannyllo Carneiro (2024)
The port sector has played a crucial role in Brazil’s resource-based economy, with its importance growing significantly over the past decade. However, this expansion has brought challenges related to sustainability. In this context, indicators have become essential for assessing port performance and implementing sustainable practices. This article proposes a sustainability index for the port sector, aligned with the Sustainable Development Goals (SDGs), and applies this model to six Brazilian ports. Data were collected through a questionnaire, with the ports anonymized and labeled as Ports A, B, C, D, E, and F. The proposed model encompasses SDGs 7, 8, 9, 11, 12, 13, 14, and 17, establishing links across 20 areas that consider the specific characteristics of the sector. The findings indicate that Ports B and E consistently demonstrate broader coverage, achieving the highest scores and reflecting comparatively more robust performance among the ports studied. SDGs 17 (Partnerships for the Goals) and 12 (Responsible Consumption and Production) appear with the highest scores when considering the averages. In contrast, SDGs 13 (Climate Action) and 7 (Affordable and Clean Energy) appear to receive less focus, representing critical areas that could benefit from increased attention within port sustainability practices, particularly for advancing clean energy initiatives and enhancing climate change adaptation efforts. This study aims to provide a robust tool for decision-makers within the sector, promoting the adoption of sustainable practices in alignment with the SDGs. Its objective is to enhance stakeholders’ understanding of the relationship between sustainability indicators and the SDGs, guiding ports on their journey towards achieving these goals.